Meneropong aktivisme digital akun @rahasiagadis melalui kajian komunikasi bermediasi komputer - Lasmery RM Girsang; Roseline (Jurnal Studi Komunikasi, 2024)
The digital era has made social media a powerful platform for social activism. One issue that is increasingly getting attention is the issue of sexual violence against women. The issue of sexual violence is one of the many issues that is of public concern because the number of acts of sexual violence is increasing along with. There were 4280 cases of sexual violence that occurred in Indonesia throughout 2023 (data collected by the Indonesia Ministry of Women's Empowerment and Child Protection). To understand this phenomenon, researchers targeted Instagram which actively highlights the issue of sexual violence that occurs in the realm of digital activism on social media. The Instagram account @rahasiagadis uses their social media platform to carry out digital activism, specifically focusing on highlighting the issue of sexual violence against women. By virtual ethnography (netnography), data collection was carried out through interviews with seven informants from @rahasiagadis and online observations (from May to August 2023) to observe the content uploaded, responses from followers, and comments that describe the involvement and views of the community on the issue of sexual violence and after that the interview data was documented verbatim. Meanwhile, data analysis relies on triangulation. By integrating a gender perspective by paying special attention to women's ways, the results of the study (which will be implications for future gender studies and digital activism) show that @rahasiagadis has succeeded in creating an active virtual community and building CMC usage goals that encourage meaningful participation and meet the psychosocial needs of followers.